REVIEW: POTENSI KETIDAKTEPATAN PENGGUNAAN OBAT PADA PASIEN GERIATRI DI BEBERAPA RUMAH SAKIT DI INDONESIA - Pratama, Gumilar; Wahyuningsih, Sri; Hermanto, Faizal (Jurnal Buana Farma, 2024)
Inappropriate medication use in geriatric patients, particularly related to Potentially Inappropriate Medications (PIMs), is a major concern in elderly healthcare management. This study aims to explore the prevalence and types of PIMs found in several hospitals in Indonesia. A narrative review method was employed, with journal data searched using the query: “Potentially Inappropriate Medications” OR “Potentially Inappropriate Prescribing”, “identification of PIMs”, “evaluation of PIMs”, “Beers Criteria” OR “Beers Criteria”, “STOPP Criteria”, “PRISCUS PIMs” in Google Scholar, Garuda, and PubMed databases. Articles selected met the inclusion criteria, including national and international journals published within the last 10 years and available in full text. The results showed that the prevalence of PIMs in a hospital in Semarang was 487 medication items, with sodium diclofenac being the most frequently found medication (12.96%). At RSUD Arjawinangun, the occurrence of PIMs reached 56.82%, with furosemide being the most dominant medication (22.73%). A study in Jakarta showed that prescription review by pharmacists successfully reduced the occurrence of PIMs to 18.89%. Inappropriate medication use in geriatric patients remains high, and it is essential to improve patient education and enhance collaboration between pharmacists and doctors to reduce PIMs risks. The use of Beers, STOPP, and PRISCUS criteria can help assess and prevent PIMs in geriatric patients.